IMPROVED WRITING ABILITY POSTER BY USING MEDIA PICTURES GRADE VIII SMP NEGERI 1 SAWO YEAR LEARNING 20 20 /20 21 - Halawa, Wirman (Al'Adzkiya Journal, 2020)
This research is motivated by the lack of students' ability in writing posters . The purpose of this study was to improve students' ability to write posters using image media . The writing method used is Classroom Action Writing (PTK). Based on the assesment which is an average student learning outcomes in the first cycle of 55 , 54 , while the average student learning outcomes p is on the second cycle of 74, 1 0. Based on this research, it can be concluded that: 1) the use of media images can improve the ability to write posters in class VIII SMP country 1 Sawo , 2) by using image media the learning process to write posters can provide good motivation to students. Suggestions are recommended: 1) the results of this study can serve as the basis for the development of the theory of learning to write and add studies theoretical writing skills , 2) expected can increase the interest in writing students through the application of media images ( 3 ) as a reference for further research.